An empirical analysis of competing explanations of urban primacy: Evidence from Asia and the Americas - Ronald L. Moomaw; Mohammed A. Alwosabi (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
This paper tests the relationship between primacy and economic development for countries in Asia and the Americas. It tests explanations for primacy drawn from several social-science disciplines–demography, economics, geography, political science, and sociology. The study is one of the first to use panel-data estimators for the tests. Economic and domestic political variables are found to be important determinants of primacy. In particular, rent-seeking and dictatorial governments are associated with primacy, but the association exists independent of the level of economic development. The implication from dependency and world-system theories that current international economic interactions promote primacy is not supported. It also examines the hypothesis that primacy first increases and then decreases with GDP per capita.
Keywords: 330; Großstadt; Bevölkerungswachstum; Wirtschaftswachstum; Schätzung; Asien; Amerika